Strategi Guru Fiqih dalam Menerapkan Karakter Religius pada Siswa di MTsN 1 Pesisir Selatan - Fithidayati, Fithidayati (Lembaga Yasin AlSys, 2023)
Instilling character in students is very important to be strengthened to fortify and improve the morale of the nation's young generation, and teachers as the spearhead of national education who play a major role in carrying out the character planting of students are expected to not stop innovating and be creative in creating effective and efficient strategies for improve the morals of students according to the goals of national education. The benefits and importance of this research are to identify the fiqh teacher's strategy in instilling religious character in students at MTsN 1 Pesisir Selatan through curricular and extracurricular activities. This study uses a qualitative approach and a descriptive type of research, taking the background at MTsN 1 Pesisir Selatan. The results of this study indicate that: The fiqh teacher's strategy in instilling religious character values in students through curricular activities is through several strategies, namely: a) Fiqh Teachers internalize religious character values into teaching materials; b) Support and control by the principal for fiqh teachers to innovate, c) Strengthening religious character; d) Implementation of learning in class through preliminary, core, and closing activities. The fiqh teacher's strategy in instilling religious character values through extracurricular activities is a) the activities of reciting juz 30 and Asmaul Husna in the morning followed by dhuha prayer in congregation, b) Tahfidzul Qur'an activities; c) tartilul qur'an activities.